1996
DOI: 10.1182/blood.v87.8.3418.bloodjournal8783418
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral blood mononuclear cells of a patient with advanced Hodgkin's lymphoma give rise to permanently growing Hodgkin-Reed Sternberg cells

Abstract: A novel Hodgkin's disease (HD) derived cell line, L1236, was established from the peripheral blood of a patient with advanced Hodgkin's disease. Analysis of immunoglobulin (Ig) gene rearrangements revealed a biallelic Ig heavy chain and a monoallelic Ig kappa light chain gene rearrangement, pointing to a B-lymphoid origin of these cells. No DNA of Epstein-Barr virus was detected in L1236. The cells expressed the HD-associated surface antigens CD30 and CD15 as well as the transferrin receptor (CD71). Cytogeneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(56 citation statements)
references
References 51 publications
1
54
0
1
Order By: Relevance
“…This individual had been treated with multiple chemotherapeutic agents (including cyclophosphamide, doxorubicin, vincristine, prednisolone, chlorambucil, bleomycin and etoposide) for lymphoma and subsequently developed caecal adenocarcinoma. SBSD resembles SBS25, (cosine similarity 0.9), previously found in Hodgkin lymphoma cell lines from two chemotherapy–treated patients 31,37 . To our knowledge this is the first time that the mutational consequences of chemotherapy have been demonstrated in normal human cells in vivo .…”
Section: Resultsmentioning
confidence: 53%
“…This individual had been treated with multiple chemotherapeutic agents (including cyclophosphamide, doxorubicin, vincristine, prednisolone, chlorambucil, bleomycin and etoposide) for lymphoma and subsequently developed caecal adenocarcinoma. SBSD resembles SBS25, (cosine similarity 0.9), previously found in Hodgkin lymphoma cell lines from two chemotherapy–treated patients 31,37 . To our knowledge this is the first time that the mutational consequences of chemotherapy have been demonstrated in normal human cells in vivo .…”
Section: Resultsmentioning
confidence: 53%
“…From the immunohistochemistry, it is thus concluded that (i) H/RS cells are proficient for hMSH2 and hMLH1 protein expression, (ii) genes encoding for hMSH2 and hMLH1 most probably are in wild-type configuration, and (iii) H/RS cells are unlikely to be MSI-high. This is conceivable with the results from our single cell study showing absence of MSI in H/RS cells in seven cases (cases [21][22][23][24][25][26][27].…”
Section: Discussionmentioning
confidence: 59%
“…The Epstein-Barr virus negative H/RS cell line L1236 was established at our institution. 25 Clonal derivation of L1236 cells from H/RS cells of the patient was demonstrated by amplification of identical Ig gene rearrangements from both sources. 26 Cells were cultured under standard conditions.…”
Section: Pathological Specimen and Cell Line L1236mentioning
confidence: 99%
“…Cell lines. H-RS cell line L1236 (Wolf et al, 1996), B-cell lymphoma line BJA-B and NIH3T3 fibroblasts were grown according to standard conditions.…”
Section: Methodsmentioning
confidence: 99%